Analysis of 1,25-dihydroxyvitamin D genomic action in human enteroids and colonoids reveals multiple regulatory effects of vitamin D in human intestinal physiology - Criss, Zachary K.; Deans-Fielder, Kali; Fleet, James C.; Christakos, Sylvia; Shroyer, Noah (Frontiers in Endocrinology, 2025)
IntroductionThe intestine has molecular and functional diversity across the proximal-distal and the crypt-villus axes, so it is imperative to determine the common and compartment-specific molecular actions of vitamin D. However, very little work on vitamin D mediated gene regulation has been done in normal human intestine. Here, we examined the impact of 1,25-dihydroxyvitamin D (1,25(OH)2D3) on cultures of human intestinal epithelium derived from duodenum (Dd) and distal colon (Co) biopsies of 6 subjects per tissue.MethodsHuman enteroids and colonoids were cultured for 3 days to promote a stem cell phenotype (undifferentiated, Un) or to induce differentiation (Diff) and then treated with vehicle control or 1,25(OH)2D3 (100 nM). 24h following treatment enteroids/colonoids were collected, RNA was isolated and RNA-seq was performed using paired-end Illumina sequencing (analysis in R using DESeq2).Results and discussionRNA-seq analysis showed that VDR mRNA is present in all four cultures tested (DdUn, DdDiff, CoUn, CoDiff) and it is not altered by 1,25(OH)2D3 treatment, intestinal segment, or differentiation status. 1,25(OH)2D3 induced the classic intestinal target genes TRPV6, ATP2B1 and CYP24A1 in all four culture groups while S100G was induced only in DdDiff. While 63 genes were vitamin D regulated across all four cultures (55 up, 8 down), we found that vitamin D regulated subgroups of genes within Dd, Co, Un, or Diff groups as well as set of genes that were unique to each culture. Functional analysis revealed several vitamin D-enriched gene ontologies or pathways including those for xenobiotic/drug metabolism in all four cultures. In differentiated cultures vitamin D induced genes were enriched for functions like regulation of barrier function through regulation of Rho GTPases and metabolism of lipids while vitamin D downregulated genes in Un groups were enriched for activities like water transport. These results provide new insight into 1,25(OH)2D3 genomic action in the functionally distinct compartments and segments of human intestine and suggest multiple regulatory effects of vitamin D in human intestinal physiology.